2008
DOI: 10.1103/physrevd.77.065006
|View full text |Cite
|
Sign up to set email alerts
|

Seiberg-Witten maps to all orders

Abstract: All order Seiberg-Witten maps of gauge parameter, gauge field and matter fields are given as a closed recursive formula. These maps are obtained by analyzing the order by order solutions of the gauge consistency and equivalence conditions as well as by directly solving Seiberg-Witten differential equations. The explicit third order non-abelian and fourth order abelian Seiberg-Witten maps of gauge parameter and gauge field are also presented..

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 17 publications
4
68
0
7
Order By: Relevance
“…On the other hand, the solution of SW-map to all orders in θ for the gauge field, matter field (both in adjoint and fundamental representation) and the gauge parameter is given in Ref. 12. These solutions match with the second order solutions given in Ref.s 6-10.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…On the other hand, the solution of SW-map to all orders in θ for the gauge field, matter field (both in adjoint and fundamental representation) and the gauge parameter is given in Ref. 12. These solutions match with the second order solutions given in Ref.s 6-10.…”
Section: Introductionsupporting
confidence: 62%
“…12, it is also shown that these solutions (22-24) can be obtained by directly solving the respective Seiberg-Witten differential equation that can be obtained by varying the deformation parameter infinitesimally θ → θ + δθ for gauge fields…”
Section: Inhomogeneous Solutions To All Ordersmentioning
confidence: 99%
“…[4] and exploiting the results of Ref. [5]. Under the analytical procedure, we take an r-θ noncommutativite parameter because the gauge fields depend on 3D radius r and on θ and, in the case of nonrotating black holes [6], [7] lead to a diagonal noncommutative analogue metric tensor.…”
Section: Discussionmentioning
confidence: 99%
“…The first order corrections for tetrads, spin connection and field strength enters in the recursive formulas, [5] …”
Section: Noncommutative Corrections For the Spinning Black Holesmentioning
confidence: 99%
“…Like in ordinary space-time, a gauge theory can be defined on a NC space-time [34] see also [35][36][37][38][39] and references therein. In the sequel, the NC variables are denoted with a "hat" notation.…”
Section: Nc Gauge Theory and Seiberg-witten Mapsmentioning
confidence: 99%